2021
DOI: 10.1097/sla.0000000000005026
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Genomic Assessment Using a Blood-based mRNA Signature (NETest) is Cost-effective and Predicts Neuroendocrine Tumor Recurrence With 94% Accuracy

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…Follow-up of GEP-NENs requires frequent endoscopy with biopsy and/or CT scanning, which causes physical pain and radiation exposure, and is costly. In the US, using a follow-up strategy with NETest resulted in a 42% saving in cost [ 82 ]. NETest would also be effective in reducing these patients’ burdens.…”
Section: Biomarkersmentioning
confidence: 99%
“…Follow-up of GEP-NENs requires frequent endoscopy with biopsy and/or CT scanning, which causes physical pain and radiation exposure, and is costly. In the US, using a follow-up strategy with NETest resulted in a 42% saving in cost [ 82 ]. NETest would also be effective in reducing these patients’ burdens.…”
Section: Biomarkersmentioning
confidence: 99%
“…In NENs, numerous transcriptomic studies have identified differentially expressed genes potentially related to tumorigenesis [ 29 31 ], while allowing to stratify NENs in new molecular subgroups, which may help to better understand their heterogeneity [ 32 ]. Moreover, efforts have been made to apply these discoveries to improve NEN diagnosis and prediction prognosis through specific tests such as the NETest [ 33 ], a gene expression assay developed to diagnose NENs based on PCR of blood-isolated RNA samples, which has evolved and is being tested to improve diagnosis and detect residual disease in NENs [ 34 , 35 ]. However, much remains to be known about the different types of RNA species and RNA-related biological processes in NENs.…”
Section: Rna Biology and Surveillancementioning
confidence: 99%
“…Furthermore, future research should assess which selection criteria should be applied for induction PRRT. These could also include new potential prognostic factors for recurrence such as loss of ATRX/DAXX, ALT-positivity [49], and α-cell origin [50], as well as predictors of response to PRRT, such as the PRRT predictive quotient [51], or of recurrence, such as the NETest [52,53].…”
Section: Discussionmentioning
confidence: 99%